2017
DOI: 10.1080/00032719.2016.1261877
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antioxidant Activity ofMomordica CharantiaFruit by Infrared-Based Fingerprinting

Abstract: Momordica charantia is widely consumed edible fruit. The food and pharmaceutical industries use it as a natural antioxidant. However, the quality control of M. charantia-based medicinal products is questionable due to the complexity of metabolites in this fruit. Hence, this study has developed a statistical model in predicting the antioxidant value through the 2, 2-diphenyl-1 picrylhydrazyl radical scavenging activity and ferric reducing antioxidant power based on infrared spectroscopy with attenuated total re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The percentage yield followed this trend 80% > 60% > 0% > 40% > 20% > 100%. The result was in agreement with [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 92%
“…The percentage yield followed this trend 80% > 60% > 0% > 40% > 20% > 100%. The result was in agreement with [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 92%
“…This result further indicated that a high proportion of methanol could be the perfect solvent for increasing extraction yields. This is in agreement with Khatib et al [ 14 ], where a higher yield of extraction was related to the water–alcohol combinations rather than the monocomponent solvent. Sultana et al [ 15 ] also reported that aqueous methanol is the most suitable solvent for extracting the leaves of a medicinal plant with a higher yield of extraction.…”
Section: Resultssupporting
confidence: 93%
“…Figure 5 demonstrates the FTIR spectra of the selected waste extracts obtained at optimum conditions, which comprises the range between 4000 and 500 cm −1 . The peaks ranging from 3010 to 3670 cm −1 correspond to the O-H stretch of the hydroxyl group, comprising biophenols and alcohols [47]. The sharper peaks observed between 3409 and 1733 cm −1 are assigned to C=O and O-H stretchings, which are attributable to oleuropein, naringin and other phenolic compounds of the leaf and peel extracts [48].…”
Section: Infrared Spectra Of the Extractsmentioning
confidence: 99%